Ответ:
Объяснение:
1.
sin (a)= (знак "-" т.к. ∈)
tg (a)=
ctg (a)= -
2.cos(a)==
tg (a)= ctg (a)=
(+)*==2.5
3.
ctg^2(a)=
cos^2(a)-sin^2(a)+1=cos^2(a)-sin^2(a)+sin^2(a)+cos^2(a)
cos^2(a)+cos^2(a)=2cos^2(a)
4.
cos^2(a)-ctg^2(a)-1+ctg^2(a)=cos^2(a)-sin^2(a)-cos^2(a)=-sin^2(a)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
1.
sin (a)=
(знак "-" т.к.
∈
)
tg (a)=![-4\sqrt{3} -4\sqrt{3}](https://tex.z-dn.net/?f=-4%5Csqrt%7B3%7D)
ctg (a)= -![\frac{1}{4\sqrt{3} } \frac{1}{4\sqrt{3} }](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%5Csqrt%7B3%7D%20%7D)
2.cos(a)=
=![\frac{\sqrt{21} }{5} \frac{\sqrt{21} }{5}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B21%7D%20%7D%7B5%7D)
tg (a)=
ctg (a)=![\frac{\sqrt{21} }{2} \frac{\sqrt{21} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B21%7D%20%7D%7B2%7D)
(
+
)*
=
=2.5
3.
ctg^2(a)=![\frac{cos^2(a)}{sin^2(a)} \frac{cos^2(a)}{sin^2(a)}](https://tex.z-dn.net/?f=%5Cfrac%7Bcos%5E2%28a%29%7D%7Bsin%5E2%28a%29%7D)
cos^2(a)-sin^2(a)+1=cos^2(a)-sin^2(a)+sin^2(a)+cos^2(a)
cos^2(a)+cos^2(a)=2cos^2(a)
4.
cos^2(a)-ctg^2(a)-1+ctg^2(a)=cos^2(a)-sin^2(a)-cos^2(a)=-sin^2(a)